2016
DOI: 10.1177/1937586716665032
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Preevaluation-Postevaluation in Health Design

Abstract: The RPPE process can be very useful when evaluating health design. It is imperative for design and healthcare professionals to use the RPPE methods to gain factual knowledge, skills, and/or attitudes of how the built environment influences a respondent's life, health, and illness and be able to translate these findings into effective healthcare designs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Studies have found that retrospective designs produce adequately valid and reliable results [29][30][31] and provide information that may be less objectively true but still important [32]. We adopted this methodology as it can allow participants to conscientiously evaluate their baseline knowledge and competencies, especially related to new subject matters, by decreasing the possibility of overestimating baseline understanding [23,33].…”
Section: Data Collectionmentioning
confidence: 99%
“…Studies have found that retrospective designs produce adequately valid and reliable results [29][30][31] and provide information that may be less objectively true but still important [32]. We adopted this methodology as it can allow participants to conscientiously evaluate their baseline knowledge and competencies, especially related to new subject matters, by decreasing the possibility of overestimating baseline understanding [23,33].…”
Section: Data Collectionmentioning
confidence: 99%
“…Mixed methods were used to examine the impact and processes of the Clinical Yarning Education program. Changes in learners’ perceived knowledge, confidence, competence and perceptions about communication in Aboriginal health care were ascertained using a retrospective pre-post questionnaire survey [ 22 , 23 ]. Following program completion learners rated themselves before the workshop (five item scale: 1 = low, 5 = high), and then after.…”
Section: Methodsmentioning
confidence: 99%
“…Following program completion learners rated themselves before the workshop (five item scale: 1 = low, 5 = high), and then after. Retrospective pre/post evaluation, measured at one point after the program, are reported to have higher validity than before/after measures because they account for changes in participants’ perspective that might occur because of the intervention, known as response shift bias [ 22 , 23 ]. The survey included demographic information (age, profession/student, previous cultural training experiences, Aboriginality) and level of agreement about program processes: how helpful learning activities were, the amount of time, how helpful for practice, and whether learners would recommend the program to others (five item scale: 1 = strongly disagree, 5 – strongly agree).…”
Section: Methodsmentioning
confidence: 99%
“…This retrospective pre–post self-evaluation tool was administered at the conclusion of the focused educational presentations. One significant benefit of using this type of self-reported retrospective data collection tool is that the participant response rate is generally higher with traditional pre- and postevaluation methods because respondents are providing pre- and postresponses at the same time, thereby limiting the possibility of withdrawing from the evaluation (Malagon-Maldonado, 2016).…”
Section: Methodsmentioning
confidence: 99%